Ekplorasi Etnomatematika Dalam Gerakan Silek Tuo Minangkabau di Bengkulu - Hidayat, Rachmat; Ramadianti, Winda; Kashardi, Kashardi (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to explore the ethnomathematic elements contained in the traditional martial arts movements of Silek Tuo Minangkabau which developed in Bengkulu. The method used is a qualitative approach with ethnographic methods, which includes problem formulation, case selection, information gathering from reliable sources, data collection through direct observation at Silek Tuo schools, in-depth interviews with professors and students, as well as visual documentation and in-depth data analysis. The results of the study indicate that several movements such as horse stances, salutes, hand strikes, baling atas, baling bawah, and batuang contain mathematical concepts, especially the concept of angles (acute, obtuse, right) and geometric shapes such as triangles. In conclusion, the movements in Silek Tuo not only represent cultural and martial values, but also have the potential as contextual media in local culture-based mathematics learning.   Keywords : Exploration, Ethnomathematics, Traditional, Silek Tuo, Minangkabau